Short enantioselective total synthesis of (R)- and (S)-pipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Kalbhor, Dinesh B. (Tetrahedron-Asymmetry, 2014)
A convenient and practical total synthesis of (R)- and (S)-pipecolic acid has been achieved by utilizing chiral cis-aziridine-2-carboxylate as the common synthetic precursor. The synthesis involves regioselective reductive cleavage of the aziridine ring and Wittig olefination as key reactions. (C) 2014 Elsevier Ltd. All rights reserved.